Anthropogenic factors and habitat complexity influence biodiversity but wave exposure drives species turnover of a subtropical rocky inter‐tidal metacommunity. (9th February 2015) - Bloch, Christopher P.; Klingbeil, Brian T.
Abstract: Coastal ecosystems are complex and species rich, but are vulnerable to degradation from a variety of anthropogenic activities. Nevertheless, information on inter‐tidal community composition in the Caribbean Basin and at other oceanic sites is lacking. Such information is essential to developing a more comprehensive understanding of rocky inter‐tidal systems and their responses to global change. The goals of this study were to determine the relative importance of environmental (wave power density, wave height), habitat ( e.g . algal cover, slope, complexity of rock surfaces) and anthropogenic (distance to roads, population density) factors associated with the structure of local assemblages at multiple shore heights and the regional metacommunity of mobile invertebrates on oceanic rocky inter‐tidal habitats. Environmental characteristics associated with habitat complexity (algal cover, rock surface complexity) and human population density were most strongly associated with abundance and biodiversity of invertebrates. Species richness was positively correlated with surface complexity, but abundance was negatively correlated with both surface complexity and per cent algal cover. By contrast, abundance of invertebrates was positively correlated with human population density, and diversity was negatively correlated with human population density. Abundance of invertebrates was greatest in the mid inter‐tidal zone, whereas diversity was greatest in the lower inter‐tidal zone. Metacommunity structure was Gleasonian, but the gradient along which species turnover occurred was correlated with measures of wave exposure, rather than anthropogenic activity. Unlike in previous studies, mostly at mainland sites, human activity primarily altered dominance patterns of communities, while having relatively little effect on species richness or composition.